Applied methods of calculations on motor vehicles - Rebrov, Oleksiy; Kalchenko, Borys; Shevtsov, Vadim; Kozhushko, Andriy; Mamontov, Anatolii (Національний технічний університет "Харківський політехнічний інститут", 2025)
At present, the problems of constructing and studying mathematical models of systems for various purposes and signals of various kinds occupy one of the leading places in modern science. The penetration of mathematical methods into engineering, natural sciences and humanities follows the path of mathematical design and modeling of the corresponding objects, and the ever-increasing capabilities of computer technology ensure the great success of this scientific direction. An important aspect of modeling is that the model must be an adequate substitute for the real situation, a real system. The model reduces the redundancy of information storage, automatically taking into account the values that correspond to the real object and characterize it, presented in the form of input and output values and state characteristics. The MATLAB system provides an intelligent environment for organizing computations for hundreds of thousands of professionals in engineering and scientific research. The MATLAB system is a leader in providing a convenient, integrated programming language for implementing a wide variety of mathematical algorithms and mathematical modeling tasks. The package also includes Simulink, a visual modeling tool that allows you to build and explore mathematical models without programming. MATLAB programming offers the greatest flexibility, richness, and convenience for solving and exploring mathematical problems. In presenting the material, preference has been given to the simplest language constructs, by studying which you can create a wide variety of non-trivial mathematical algorithms.
Keywords: methodological instructions; laboratory work; motor vehicles; applied methods of calculations; automobile transport; mechanical engineering